A LEGISLAÇÃO SOBRE O CICLO PRODUTIVO DO ÓLEO DE Cannabis sativa L. PARA FINS MEDICINAIS: - (CIPEEX, 2026)
The regulation of Cannabis sativa L. for medicinal purposes has produced significant social and scientific impacts. This study aimed to: (i) identify and analyze the main national and international legal frameworks for medicinal cannabis; (ii) examine the development of legislation applicable to the cannabis oil production cycle; and (iii) assess the qualifications of dentists to prescribe cannabis-derived products. This is a bibliographic, documentary, and qualitative review, using data obtained from scientific databases (PubMed, SciELO, Web of Science) and legislation from ANVISA, the Federal Council of Medicine (CFM), and the Federal Council of Dentistry (CFO). The results showed that countries such as Canada, Israel and Uruguay have advanced in the standardization of medicinal Cannabis, while in Brazil the evolution occurred in a fragmented manner, through Law No. 11,343/2006, ANVISA Resolutions (RDC No. 327/2019, No. 335/2020 and No. 660/2022) and CFO Resolution No. 82/2008. It is concluded that, despite the advances, there are still challenges regarding universal access, dependence on imports and the need to regulate national cultivation.
Keywords: Cannabis sativa L.; potencial terapêutico; regulamentação nacional; profissionais da saúde